Particle size distribution of the major Alternaria alternata allergen, Alt a 1, derived from airborne spores and subspore fragments. Issue 3 (March 2020) - Grewling, Łukasz; Bogawski, Paweł; Szymańska, Agata; Nowak, Małgorzata; Kostecki, Łukasz; Smith, Matt
Abstract: Fungal fragments are abundant immunoreactive bioaerosols that may outnumber the concentrations of intact spores in the air. To investigate the importance of Alternaria fragments as sources of allergens compared to Alternaria spores, we determined the levels of Alternaria spores and Alt a 1 (the major allergen in Alternaria alternata spores) collected on filters within three fractions of particulate matter (PM) of different aerodynamic diameter: (1) PM>10, (diameter>10 μm); (2) PM2.5-10 (2.5–10μm); (3) PM2.5 (0.12–2.5 μm). The airborne particles were collected using a three stage high-volume ChemVol cascade impactor during the Alternaria sporulation season in Poznań, Poland (30 d between 6 July and 22 September 2016). The quantification of Alt a 1 was performed using the enzyme-linked immunosorbent assay. High concentrations of Alt a 1 were recorded during warm and dry d characterized by high sunshine duration, lack of clouds and high dew point values. Atmospheric concentrations of Alternaria spores correlated significantly (r = 0.930, p < 0.001) with Alt a 1 levels. The highest Alt a 1 was recorded in PM2.5-10 (66.8 % of total Alt a 1), while the lowest in PM2.5 (<1.0 %). Significantly more Alt a 1 per spore (>30 %) was observed in PM2.5-10 than in PM>10 . This Alt a 1 excess may be derived from sources other than spores, e.g. hyphal fragments. Overall, in outdoor air the major source of Alt a 1 are intact Alternaria spores, but the impact of other fungal fragments (hyphal parts, broken spores, conidiophores) cannot be neglected, as they may increase the total atmospheric Alt a 1 concentration. Graphical abstract: Image 1 Highlights: Alt a 1 (major allergen of Alternaria ) was quantified in different air fractions. Alternaria spores and Alt a 1 levels correlated significantly (r = 0.930, p < 0.001). The highest Alt a 1 level was detected in PM2.5-10, while the lowest in PM2.5 Significantly more Alt a 1 per spore (31.3 %) was observed in PM2.5-10 than in PM>10 . Spores are the main source of Alt a 1, but the impact of hyphae cannot be neglected.